Iris biometric model for secured network access - Khoury, Franjieh El. (Boca Raton : CRC Press, 2013)
'The rapid evolution of technology in the computer world has made securing access to confidential data a very important issue in terms of research. This technology is likely to evolve in various architectures. Each architecture has its own functionality, its advantages and disadvantages. On the one hand the transition from a centralized to a decentralized system distributed locally or remotely, has facilitated the tasks in various sectors (i.e., educational, social, government, commercial, etc.). On the other hand, the integration of the Internet has encouraged communication at international level, and allowed operations remotely (i.e., e-commerce, e-banking, etc.). Besides the Internet, there is the mobile network that provides advanced services (i.e., multimedia messaging, Internet access, etc.)'--
Part 1: State of the art -- Security of computer networks -- Biometric systems -- Cryptography -- Multiagent system -- Part 2: Critical analysis of methods of iris recognition -- Existing methods for localization of external and internal edges of the iris of the eye -- Existing methods for eliminating effects of the eyelids -- Part 3: Our proposed model : the iris crypto agent system -- Biometric model for authentication using the iris of the eye -- Global model integrating a multiagent system -- Part 4: Implementation and simulations -- Implementations of new methods -- Simulation of modules -- Application.
Includes bibliographical references and index.
Keywords: Biometric identification; Iris (Eye).; Computer networks -- Security measures